Staffing of judicial institutions under the judicial reform of 1864 - Prylipko, Serhii; Korolyova, Viktoriya; Прилипко, Сергій Миколайович; Корольова, Вікторія Вікторівна; Корольова, Вікторія; Прилипко, Сергій (ТОВ "Наукова установа "Правові горизонти", 2025)
The article analyzes the staffing of judicial institutions under the judicial reform of 1864. It is noted that the judicial reform was initiated in connection with the need to update the legislation and introduce new principles for the functioning of judicial institutions, and the main goal of the reform was to create a democratic court based on the traditions of the judiciary of European countries. It is emphasized that among the important innovations of the reform was the creation of peace and general justice, which covered most criminal and civil cases. It is noted that the peace courts functioned as a separate system, different from the general courts, with their own legal regulation, which included the involvement of peasants in civic life, emphasizing the equality of all before the law. It is emphasized that an important aspect of the reform was the election of justices of the peace, which ensured control over the electoral process, and elections were held by county zemstvo assemblies or city dumas, taking into account age, educational and property qualifications. It is noted that certain restrictions were established for candidates for the position of justice of the peace regarding persons who were under investigation, convicted of crimes, as well as those who were dismissed from service, which was aimed at ensuring the integrity and professionalism of judges in the new system. It is noted that in the conditions of the judicial reform, there was a clear shortage of qualified personnel, since the majority of judges had only a gymnasium education, which turned out to be insufficient for effective judicial activity. It is noted that judicial activity during the implementation of the reform became an independent sphere, which required reforming the mechanism for selecting judges, and therefore physical, social, moral and intellectual conditions were established for members of district courts. It is stated that the reform of judicial statutes introduced a new procedure for recruiting judges, which ensured their independence and professionalism. At the same time, it is substantiated that the introduction of mandatory legal education for judges increased the level of professionalism in the judicial system. It is also emphasized that the irremovability of judges and their financial security became important conditions for ensuring the independence of judges, judges could be transferred only with their own consent, and dismissal was possible only by court decision.
Кадрове забезпечення судових установ у період судової реформи 1864 року
Keywords: staffing; court; judges; judicial reform of 1864; judicial statutes